Phases of functional, near-normoglycaemic insulin substitution: what are computers good for in the rehabilitation process in type I (insulin-dependent) diabetes mellitus? - Howorka, K.; Thoma, H.; Grillmayr, H.; Kitzler, E. (Computer methods and programs in biomedicine, 1990)
We have divided the rehabilitation process in patients with insulin-dependent diabetes mellitus into the following four phases. The basic phase, the so-called ‘phase 0’, provides information about literature, different strategies of treatment and introduces the use of regular insulin as well as blood sugar self-monitoring. During the ‘phase 1’ (i.e. ‘diabetes education common sense’) all the initial information from ‘phase 0’ will be used practically and discussed in depth. After the patient's actual insulin need (U/24 h) has been estimated, initial algorithms for functional insulin use can be defined. And this is the turning point to ‘phase 2’ of the group rehabilitation process, the so-called education in functional insulin use. Initial algorithms should be understood as a preliminary answer to the patient's questions, ‘What is my basal insulin need?’, ‘How much insulin do I need for a particular amount of carbohydrates?’, and ‘What is the hypothetical response of my blood glucose to a particular amount of insulin?’. These algorithms are going to be used and optimised now by the patient (under the supervision of the physician) during the so-called ‘insulin games’ (fasting or 24 h, experimental violation of traditional dietary rules, etc.) to demonstrate (1) how to influence actual glycaemia through immediate correction of blood sugar off blood sugar target (primary adjustment of insulin dosing), and (2) how to optimise algorithms for insulin use (secondary insulin adjustment) in future conditions of different insulin sensitivity. The ‘phase 3’ of individual teaching is an ongoing process of updating the patient's knowledge and practical skills. All these phases (0–3) usually require about 40–50 h of (group) teaching. Functional insulin substitution was proposed for 340 type I diabetic patients. The mean glycosilated haemoglobin decreased to the upper limit of normal range in out-patients under the condition of free diet and remains still in this range despite low frequency of acute complications (Diabetologia 30 (1987) 47–48; p < 0.0001 vs. initial values). Computers are used for experimental purposes in all these phases of the rehabilitation process: (1) for the initial (programmed) information (‘phase 0’), (2) for estimation of initial algorithms (‘phase 1’), (3) as a training computer in the blood sugar simulation process (‘phase 2’), and (4) for statistical evaluation of out-patients' clinical data and for up-dating the patient's knowledge (‘phase 3’), as an ‘artificial diabetes counsellor’. However, computers are still not used by the patient on a routine basis at present.